Evaluasi sistem organisasi olahraga dan kinerja atlet floorball Persatuan Floorball Indonesia - Khuddus, Lutfhi Abdil; Arja Bahauddin, Muhammad; Dwi Adi Priyanto, Yongky; Bing, Liu; Perwira Bakti, Ananda (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
The coaching program with outstanding achievements has indeed been implemented based on the objectives of the coaching itself and the critical factors contained in a program. Factors from an organizational system that is not good can also affect achievement results. With appropriate stages and fulfilling these factors, it is hoped that achievement will be more easily achieved. Looking at the introduction above, it is clear that Indonesian floorball still has many obstacles in its sports management system. Still needs to be developed in all regions of Indonesia. Besides that, Indonesian floorball athletes' performance is considered less able to match Asian countries. Hence, this study aims to evaluate the sports organization system and the implementation of floorball athletes in the Indonesian Floorball Association. The objects of this research include the Chairperson of Floorball at the central and regional levels, the Secretary, the Treasurer, the Coach, and 96 athletes who competed in the big eight rounds of the national floorball championship in Jakarta. Data was collected using the mixed method by administering a CIPP questionnaire and giving physical test items to floorball athletes. The output of this research is an evaluation of the sports organization system in which policymakers can improve and create a good formula so that the future organization can be better so that floorball athletes' achievements can increase.